2019
DOI: 10.3390/jcm8101521
|View full text |Cite
|
Sign up to set email alerts
|

Motor Capacities in Boys with High Functioning Autism: Which Evaluations to Choose?

Abstract: The difficulties with motor skills in children with autism spectrum disorders (ASD) has become a major focus of interest. Our objectives were to provide an overall profile of motor capacities in children with ASD compared to neurotypically developed children through specific tests, and to identify which motor tests best discriminate children with or without ASD. Twenty-two male children with ASD (ASD—10.7 ± 1.3 years) and twenty controls (CONT—10.0 ± 1.6 years) completed an evaluation with 42 motor tests from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
7
0
1
Order By: Relevance
“…The present study focused on the sleep and physical activities assessments of children with ASD to evaluate the effect of PA level on sleep quality in children with ASD. As already reported by many authors, our results confirmed that children with ASD showed poor sleep indices related to PA level [ 11 , 16 , 18 , 19 , 28 , 29 , 30 ]. The recommended amount of sleep needed for optimal health, as suggested by pediatric experts, is 8 to 10 h of sleep for all children, with or without ASD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study focused on the sleep and physical activities assessments of children with ASD to evaluate the effect of PA level on sleep quality in children with ASD. As already reported by many authors, our results confirmed that children with ASD showed poor sleep indices related to PA level [ 11 , 16 , 18 , 19 , 28 , 29 , 30 ]. The recommended amount of sleep needed for optimal health, as suggested by pediatric experts, is 8 to 10 h of sleep for all children, with or without ASD.…”
Section: Discussionsupporting
confidence: 92%
“…The recommended amount of sleep needed for optimal health, as suggested by pediatric experts, is 8 to 10 h of sleep for all children, with or without ASD. Nevertheless, some studies have reported shortened total sleep duration associated with difficulty falling asleep, frequent night-time awakening, and early morning awakening in children with ASD [ 4 , 5 , 7 , 29 ]. These sleep disorders occurred in 44% to 83% of children, which represents a major problem for parents [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were also in line with previous findings [9,10,17]. Bricout et.al [18] showed that people with autism are different from the control group in motor skills like handicrafts and rolling the ball. It should be noted that children with autism are different from healthy children in motivations and their performance will be weak if they have not enough motivation [19].…”
Section: Discussionsupporting
confidence: 92%
“…In the same study, it was shown that the fitness level of children with ASD was not related to income, maternal education, or ethnic origin (Tyler etal., 2014). Previous research indicates that children and/or adolescents with mild to moderate autism have lower fitness parameters (speed, coordination, flexibility, strength, and power) and lower PA levels compared with their TD peers (Bricout etal., 2018; Bricout etal., 2019; Pan etal., 2016; Tyler etal., 2014).…”
Section: Discussionmentioning
confidence: 99%